Engaging the multi-generational workforce in tourism and hospitality. Issue 4 (11th November 2014) - Barron, Paul; Leask, Anna; Fyall, Alan
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this study is to present strategies that hospitality and tourism organisations might adopt as a means of encouraging employee engagement, thus enabling the more effective management of an increasingly multi-generational workforce. This paper evaluates current strategies being adopted that might encourage employee engagement by a selection of hospitality and tourism organisations and develop recommendations for organisations wishing to more effectively engage the multi-generational workforce. Design/methodology/approach – This study adopts a mixed methods approach and presents findings based on a series of semi-structured interviews with management and self-completion questionnaires aimed at employees. Findings – The relationship between the supervisor and the employee remains a key enhancer regarding engagement and employees are increasingly demanding more contemporary methods of communication. Employers should take note of generational characteristics and adopt flexible policies attractive to all employees. Practical implications – This paper contributes no t only to the debate regarding generational differences in the workplace but it also identifies that the various generations evident in tourism organisations are desirous of similar working conditions and benefits. Organisations should consider the development of a range of packages that focus on linking employees with their purpose, their colleagues and their resources as a means of encouraging employee engagement. Originality/value – This study contributes to the debate regarding employee engagement and compares and contrasts initiatives that various tourism and hospitality organisations are adopting as a means of encouraging employee engagement. The study also elicits the views of the organisations employees to understand the extent of the effectiveness of such initiatives and makes recommendations regarding the most effective initiatives from both a management and employee perspective.